THE EFFECTIVENESS OF USING MEMRISE APPLICATION IN TEACHING VOCABULARY - Ai Siti Nuralisah; Evie Kareviati (PROJECT (Professional Journal of English Education), 2020)
This research is based on the use of the Memrise application in a vocabulary study of seventh-grade students. This research was carried out based on a preliminary study which showed that students had difficulty learning English because of the lack of understanding of the vocabulary they had, and the method used by the teacher to teach vocabulary is still in a conventional way. The subjects of this study were 35 students consisting of 28 male and 10 female seventh-grade students of SMPN 1 Cililin. The purpose of this study is to improve students' understanding and achievement of vocabulary through the use of the Memrise application. Vocabulary tests and questionnaires were used as the instruments of eliciting the data. The results of the test and questionnaire study showed an increase in grades, and students' interest and motivation after using the memrise application in vocabulary learning. From the results obtained, it was concluded that memrise application is recommended to be used as an alternative method in teaching vocabulary. Besides students, with this Memrise application, it can add to the teacher's insight about the use of methods in teaching in the classroom.